Utilization of CT perfusion patient selection for mechanical thrombectomy irrespective of time: a comparison of functional outcomes and complications. (30th August 2012) - Turk, Aquilla S; Nyberg, Eric MacKenzie; Chaudry, M Imran; Turner, Raymond D; Magarik, Jordan Asher; Nicholas, Joyce S; Holmstedt, Christine A; Chalela, Julio Alejandro; Hays, Angela; Lazaridis, Christos; Chimowitz, Marc I; Turan, Tanya N; et al.
Abstract : Background: Patient selection for acute ischemic stroke has been largely driven by time-based criteria, although emerging data suggest that image-based criteria may be useful. The purpose of this study was to directly compare outcomes of patients treated within a traditional time window with those treated beyond this benchmark when CT perfusion (CTP) imaging was used as the primary selection tool. Methods: A prospectively collected database of all patients with acute ischemic stroke who received intra-arterial therapy at the Medical University of South Carolina was retrospectively analyzed, regardless of time from symptom onset. At presentation, CTP maps were qualitatively assessed. Selected patients underwent intra-arterial therapy. Functional outcome according to the modified Rankin scale (mRS) score at about 90 days was documented. Results: 140 patients were included in the study. The median time from symptom onset to groin access was 7.0 h. Overall, 28 patients (20%) had bleeding complications, but only 10 (7.1%) were symptomatic. The average National Institute of Health Stroke Scale (NIHSS) score for patients treated ≤7 h from symptom onset was 17.3 and 30.2% had a mRS score of 0–2 at 90 days. Patients treated >7 h from symptom onset had an average NIHSS score of 15.1 and 45.5% achieved a mRS score of 0–2 at 90 days (p=0.104). Patients in the two groups had similar rates of symptomatic intracerebral hemorrhage (8.5% and 5.8%, respectively; p=0.745). Conclusions: No difference was found in the rates of good functional outcome between patients treated ≤7 h and those treated >7 h from symptom onset. These data suggest that imaging-based patient selection is a safe and viable methodology.